Pengaruh Model Pembelajaran PACE terhadap Kemampuan Pemahaman Konsep Matematika Siswa Kelas XI - Desty Haswati; Riska Nur Aini; Selpiyani Selpiyani; Utari Nur Permadi (Jurnal Tadris Matematika, 2019)
Understanding mathematical concept is one of ability to rediscover knowledge that has been obtained, both orally and a written. The purpose of this research was to compare the ability to understand mathematical concept of student who taught with the PACE (Project, Activity, Cooperative, Exercise) learning model and conventional learning model. A quass-experimental design combined with experimental method purposed in this research. The population in this research were all students of class XI SMA 15 Kota Tangerang by taking a sample of 2 classes, that is class MIPA 5 as an experimental class and class MIPA 2 as an control class. The sampling technique uses purposive sampling technique. The research instrument used a test of the ability to understand mathematical concepts. Mann Whitney test is used to test the hypothesis. The results of this research are students’s ability to understand a mathematical concepts taught with a PACE learning model higher than conventional learning models.